Efektivitas Pemungutan Pajak Bumi dan Bangunan Perdesaan dan Perkotaan di Wilayah Kerja UPTD Pelayanan Pajak Daerah Wilayah III Ciparay - Al'libani, Ridha Rahim; Prayoga, Indra Aditya; Mulyana, Asep (RIGGS: Journal of Artificial Intelligence and Digital Business, 2024)
This research aims to measure the effectiveness of collecting Rural and Urban Land and Building Tax (PBB-P2) in the Work Area of the Regional Tax Service Unit III Ciparay, with a focus on tax collection effectiveness. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews with key informants from various levels of local government, including UPTD Tax staff, sub-district governments, and village governments. Field observations were conducted to directly understand the implementation of tax policies on the ground, while document studies were used to obtain historical and regulatory information. The factors explored in this study include understanding of the tax program, tax compliance, implementation timing, achievement of program goals, and tangible changes produced. The research results indicate that despite challenges such as low public awareness and lack of inter-agency coordination, the implementation of intensive socialization strategies, strengthening the tax information system, and better coordination have improved the effectiveness of PBB-P2 collection. This research provides recommendations for further improvements in socialization, coordination, and strengthening of support systems to support the achievement of tax targets and sustainable regional development. Thus, this research makes an important contribution to understanding effective strategies for improving tax collection at the local level and its relevance in the context of local government in Indonesia.